2019
DOI: 10.1111/anec.12702
|View full text |Cite
|
Sign up to set email alerts
|

The effect of idiopathic premature ventricular complexes on left ventricular ejection fraction

Abstract: Aim Current literature lacks a definitive threshold of idiopathic premature ventricular complex (PVC) burden for predicting cardiomyopathy (CMP). The main objective of the present study was to evaluate relationship between the PVC burden and left ventricular ejection fraction (LVEF). Method This multicenter, cross‐sectional study included 341 consecutive patients with more than 1,000 idiopathic PVC in 24 hr of Holter monitoring admitted to the cardiology clinics between January 2019 and May 2019 in the ninetee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 41 publications
0
9
0
Order By: Relevance
“…Approximately 70% of them originate from the RVOT [3] , [8] and the remaining from the LVOT and adjacent structures such as pulmonary artery, the ASV and LV summit [12] , [6] , [7] , [8] . It has been shown that a high burden of PVCs is associated with a decline in LV ejection fraction (LVEF) [13] , [14] . According to the latest guidelines, CA is recommended for the treatment of Vas originating from the cardiac OT in symptomatic patients or in those exhibiting arrhythmia-induced cardiomyopathy [3] , [4] .…”
Section: Discussionmentioning
confidence: 99%
“…Approximately 70% of them originate from the RVOT [3] , [8] and the remaining from the LVOT and adjacent structures such as pulmonary artery, the ASV and LV summit [12] , [6] , [7] , [8] . It has been shown that a high burden of PVCs is associated with a decline in LV ejection fraction (LVEF) [13] , [14] . According to the latest guidelines, CA is recommended for the treatment of Vas originating from the cardiac OT in symptomatic patients or in those exhibiting arrhythmia-induced cardiomyopathy [3] , [4] .…”
Section: Discussionmentioning
confidence: 99%
“… b Represents the follow-up period range using mean/median years (or months [mo] when indicated). References not reporting the follow-up timeframe [ 36 , 44 , 48 , 55 , 62 , 63 , 65 , 82 , 91 , 93 ]. Details on follow-up period for all studies are available in S3 Table .…”
Section: Resultsmentioning
confidence: 99%
“…PVC morphology has also been associated with a lower LVEF. For example, patients with a lower LVEF have PVCs that are either notched or have a wide shelved QRS [ 93 ], or have a greater coupling interval and longer PVC QRS duration [ 64 , 82 ]. Studies show that there is a higher prevalence of LV dysfunction in patients with frequent PVCs (≥ 10 PVCs/hour or > 1,000 PVCs/day) [ 49 , 103 ] or a high burden of PVCs (i.e., PVCs >30% of all beats/day) [ 60 ], indicating PVCs are a marker of LV dysfunction.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… 4 However, this study did identify a patient with PVC burden of 10% with a PVC cardiomyopathy 4 ; this correlates with findings from other studies with a PVC burden as low as 5%–6% causing a PVC cardiomyopathy. 5 , 6 , 7 This is a sobering finding, since the PVC burden has been identified as our most reliable criterion for identifying patients at risk, so proper vigilance requires monitoring patients carefully for PVC burdens of ≥5%. Part of this variability in PVC burden and its association with PVC cardiomyopathy may be other contributing factors that include male sex, asymptomatic PVCs, repetitive monomorphic ventricular tachycardia, variability of the PVC coupling interval, PVC duration >150 ms, and epicardial PVC origin.…”
Section: How Many Pvcs Are Too Many?mentioning
confidence: 99%